Application of seismic reflections surveys for deep exploration - A case from the gawler craton iron oxide cu-au deposits - Okan, Evans; Kepic, Anton; Urosevic, Milovan (2016)
Potential and geological methods are traditionally used to discover Cu-Au deposits. Whilst these methods seem effective, they lack resolution needed to confidently detect deeper mineral deposits. As the search for ore-bodies under regolith cover expands due to depletion of the near surface deposits, there is need to develop new exploration technology to explore these ore-bodies within 1-3km depth range. Seismic reflection method represents this new technology as it offers distinct advantage over all other geophysical techniques because of its depth of penetration and superior spatial resolution. Further, in many different geological environments, it offers a greater "3D mapability" of units within the stratigraphic column. We present two prospect case studies within the Gawler craton (Olympic Dam and Vulcan) deposits. Results show that seismic method could be a useful tool for exploration of deep seated IOCG deposits. The migrated section was not only able to identify and trace various and the complex structures but also shows reflections around the edges of intrusion. In the case of Gawler Craton, IOCG deposits tend to be a later addition to the regional metamorphic events hence seismic reflection surveys might be good for such exploration especially along known faults or edges of major intrusive complexes.